Azimuthal emission patterns of K+ and of K- mesons in Ni + Ni collisions near the strangeness production threshold - Zinyuk, Victoria; Kang, T. I.; Leifels, Y.; Herrmann, Norbert; Hong, B.; Averbeck, R.; Andronic, A.; Barret, V.; Basrak, Z.; Bastid, N.; Benabderrahmane, M. L.; Berger, M.; et al. (Physical review. C, Nuclear physics, 2014)
Azimuthal emission patterns of K± mesons have been measured in Ni + Ni collisions with the FOPI spectrometer at a beam kinetic energy of 1.91 A GeV. The transverse momentum pT integrated directed and elliptic flow of K+ and K− mesons as well as the centrality dependence of pT - differential directed flow of K+ mesons are compared to the predictions of hadron string dynamics and isospin quantum molecular dynamics transport models. The data exhibits different propagation patterns of K+ and K− mesons in the compressed and heated nuclear medium and favor the existence of a kaon-nucleon in-medium potential, repulsive for K+ mesons and attractive for K− mesons.
Im Titel sind + und - hochgestellt
Gesehen am 09.09.2020